2009
DOI: 10.1002/hipo.20610
|View full text |Cite
|
Sign up to set email alerts
|

The hippocampus contributes to memory expression during transitive inference in mice

Abstract: There is substantial evidence that the hippocampus plays a role in transitive inference, the capacity to link overlapping memories and subsequently make novel judgments between elements of those memories that are only indirectly related. However, it is unclear whether the hippocampus is involved primarily during the original acquisition of the overlapping memories, or additionally during the flexible expression of those memories during transitive judgments. Here, we demonstrated that selective hippocampal dama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 34 publications
4
50
1
Order By: Relevance
“…DeVito et al (2010) found that animals with hippocampal lesions and sham-operated controls exhibited the same pattern of performance on the odor pairs, such that performance on the context-dependent BC and CD discriminations was lower than performance on the AB and DE pairs; however, the animals with hippocampal damage exhibited higher levels of performance on the end-anchored (AB and DE) discriminations as compared to controls. In this study, both sham-operated animals and animals with prefrontal damage exhibited very different patterns of performance.…”
Section: Impaired Relational Memory Due To Dysfunction Of the Hippocamentioning
confidence: 85%
See 3 more Smart Citations
“…DeVito et al (2010) found that animals with hippocampal lesions and sham-operated controls exhibited the same pattern of performance on the odor pairs, such that performance on the context-dependent BC and CD discriminations was lower than performance on the AB and DE pairs; however, the animals with hippocampal damage exhibited higher levels of performance on the end-anchored (AB and DE) discriminations as compared to controls. In this study, both sham-operated animals and animals with prefrontal damage exhibited very different patterns of performance.…”
Section: Impaired Relational Memory Due To Dysfunction Of the Hippocamentioning
confidence: 85%
“…Recent studies have demonstrated that the hippocampus itself is initially critical to the transitive judgment ( Van der Jeugd et al 2009;DeVito et al 2010). DeVito et al (2010) found that damage to the hippocampus produced even after the animals had demonstrated successful transitive performance still impairs the ability to perform transitive inference; however, an additional 1-wk test revealed a partial recovery in relational memory abilities. In contrast to these results, Van der Jeugd et al (2009) demonstrated that damage to the hippocampus prior to learning, and not after the pairs had been learned, resulted in a deficit in transitive inference judgments.…”
Section: Impaired Relational Memory Due To Dysfunction Of the Hippocamentioning
confidence: 99%
See 2 more Smart Citations
“…Davis (1992) has developed this test version for rats. Although extensively used to evaluate the role of the hippocampus (Dusek and Eichenbaum, 1997;Eichenbaum et al, 1999;Devito et al, 2010a) and the prefrontal cortex (Devito et al, 2010b) in relational memory, to our knowledge this test has never been used to assess the effect of drugs affecting cognitive domains disturbed in schizophrenia. Phencyclidine (PCP) is a drug that produces a number of cognitive disturbances, including cognitive inflexibility .…”
Section: Introductionmentioning
confidence: 99%